2021
DOI: 10.1155/2021/9019334
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Drilling Behaviour of Synthetic and Natural Fiber‐Based Composites

Abstract: For comparison, the drilling behaviour of abaca fiber-reinforced polymer (AFRP) composites and Kevlar-reinforced epoxy polymer (KFRP) composites has been studied in the specified experimental condition. The different geometrical drilling tools have been used for the investigation, namely, candlestick (T1), core (T2), standard twist drill (T3), and step cone (T4). The tool feed of 30, 45, and 60 m/min and rotational speed of 1000, 1500, and 2000 rpm have been used for the investigation. The thrust force is chos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 39 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…The major challenge in processing aluminium-based alloys in SLM is reflectivity, low melting point, and interaction with oxygen in the environment [ 15 , 38 , 107 109 ]. Only 10% of the input energy is utilized to melt the powder, and the remaining is reflected.…”
Section: Inferences and Discussionmentioning
confidence: 99%
“…The major challenge in processing aluminium-based alloys in SLM is reflectivity, low melting point, and interaction with oxygen in the environment [ 15 , 38 , 107 109 ]. Only 10% of the input energy is utilized to melt the powder, and the remaining is reflected.…”
Section: Inferences and Discussionmentioning
confidence: 99%
“…Drilling natural fiber composites is a critical step in the production of natural products. In the most of drilling of natural fiber composites, the influences of various drilling parameters on the delamination factors and surface damages were only discussed [40,41]. In this research, two drilling characteristics, ovality and delamination factors are discussed to enhance the fabrication characteristics using natural fibers.…”
Section: Analysis Of Drilling Characteristicsmentioning
confidence: 97%
“…There are also some studies specifically comparing synthetic and natural fiber's drilling behaviors. In particular, studies comparing Kevlar-and abaca-reinforced composites during machining have suggested that it is possible to apply different drill geometries, namely, candlestick and core bits, and still obtain appropriate performance, although the thrust forces are markedly different (28.6 N for abaca and 63.18 N for Kevlar composites) [31].…”
Section: Drilling Of Synthetic and Natural Fiber Composites: Specific...mentioning
confidence: 99%